2011
DOI: 10.1021/nl200722z
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering in Cubic Cerium Oxide Nanostructures for Catalytic Oxidation

Abstract: Traditional nanostructured design of cerium oxide catalysts typically focuses on their shape, size, and elemental composition. We report a different approach to enhance the catalytic activity of cerium oxide nanostructures through engineering high density of oxygen vacancy defects in these catalysts without dopants. The defect engineering was accomplished by a low pressure thermal activation process that exploits the nanosize effect of decreased oxygen storage capacity in nanostructured cerium oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
245
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(254 citation statements)
references
References 39 publications
6
245
0
3
Order By: Relevance
“…AC-HRTEM studies providing sub-angstrom resolution [22,24], clearly revealed (111) crystal planes exposed at ceria rods and particles [25,31,62,63], whereas ceria cubes are enclosed by mainly (100) facets [18]. These ceria nanoshapes exhibited exactly the same trends in activity per surface area for WGS reaction (decreasing from ceria cubes to rods and finally particles) as reported in this study on RWGS reaction (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…AC-HRTEM studies providing sub-angstrom resolution [22,24], clearly revealed (111) crystal planes exposed at ceria rods and particles [25,31,62,63], whereas ceria cubes are enclosed by mainly (100) facets [18]. These ceria nanoshapes exhibited exactly the same trends in activity per surface area for WGS reaction (decreasing from ceria cubes to rods and finally particles) as reported in this study on RWGS reaction (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…17 Localized electrons on the occupied 4f-orbital of Ce 3+ ions contribute to the electronic interaction between reduced CeO 2 and supported Au NPs. 15,19 CeO 2 -supported Au is regarded as a promising catalytic system, because it combines highly active components, Au NPs and CeO 2 .…”
Section: +mentioning
confidence: 99%
“…18 Lawrence et al recently demonstrated that catalytic activity is a function of the concentration of oxygen vacancies for the CO oxidation activity of CeO 2 nanorods, NPs, and the bulk surface. 17 Oxygen vacancy formation on the CeO 2 surface accompanies the reduction of adjacent Ce 4+ ions to Ce…”
Section: ■ Introductionmentioning
confidence: 99%
“…This leads to the relative stability of the low index ceria surfaces following the trend: (111) [ (110) [ (100), but the formation energies of oxygen vacancies on different planes of ceria vary, following the order: (110) \ (100) \ (111), and the frequency of use of crystalline planes has the order: (100) \ (110) \ (111). So, the higher catalytic activity is due to the exposed (100) and (110) planes (form of particles: spindle-shaped, rods, cubes), but ceria nanoparticles preferentially expose stable (111) planes (Wu et al 2012;Lawrence et al 2011;Na et al 2008;Mai et al 2005;Lundberg et al 2004;Sayle et al 2002). FTIR spectra (Fig.…”
Section: Resultsmentioning
confidence: 97%